Vapor-liquid equilibria for the systems difluoromethane plus chlorodifluoromethane, difluoromethane plus dichlorodifluoromethane, and difluoromethane plus chloromethane at 10.0 degrees C - Kang, YW; Chung, KY (AMER CHEMICAL SOC, 1996)
Isothermal vapor-liquid equilibria for the three binary systems (difluoromethane + chlorodifluoromethane, difluoromethane + dichlorodifluoromethane, and difluoromethane + chloromethane) have been measured at 10.0 degrees C. The experimental data for the binary systems are correlated with the Wilson equation and the relevant parameters are presented. The difluoromethane + dichlorodifluoromethane system forms a minimum boiling azeotrope, but the others do not.
Keywords: EQUATION